2020
DOI: 10.1093/heapol/czaa039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a prospective payment method for health facilities on direct medical expenditures in a low-resource setting: a paired pre-post study

Abstract: Almost all sub-Saharan countries have adopted cost-reduction policies to facilitate access to health care. However, several studies underline the reimbursement delays experienced by health facilities, which lead to deficient implementation of these policies. In April 2016, for its free care policy, Burkina Faso shifted from fee-for-service (FFS) paid retrospectively to FFS paid prospectively. This study tested the hypothesis that this new method of payment would be associated with an increase in direct medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…A before-and-after study in Burkina Faso showed that both government and household expenditure on CS increased after the free delivery policy changed from retrospective fee-for-service payment to prospective fee-for-service payment. 82 The other study showed that the introduction of performancebased financing at DHs in Rwanda was associated with an increase in the number of CS from 60 to 140 per quarter over a 5-year period. 83…”
Section: Open Accessmentioning
confidence: 94%
“…A before-and-after study in Burkina Faso showed that both government and household expenditure on CS increased after the free delivery policy changed from retrospective fee-for-service payment to prospective fee-for-service payment. 82 The other study showed that the introduction of performancebased financing at DHs in Rwanda was associated with an increase in the number of CS from 60 to 140 per quarter over a 5-year period. 83…”
Section: Open Accessmentioning
confidence: 94%
“…It was also reported in the same study in some countries (India, Pakistan, Bangladesh) that while outpatient treatment services were more inexpensive in private HCPs, inpatient treatment services were more inexpensive in public HCPs (Saksena et al, 2012). In a study that investigated the effects of the prospective fee-forservice payment method for payments made to HCPs in Burkina, it was found that there was an increase in the medical spending of HCPs as a result of the transition in 2016 from fee-forservice paid retrospectively to fee-for-service paid prospectively (Meda et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to the gradual increase in medical expenditures each year, insurance institutions in many countries, such as Germany, Canada, Japan, Taiwan, etc., have adopted a prospective payment system (PPS) to control the increasing expenditures [1]. In the past, the payment system for health insurance has worked on a fee-for-service policy, which may have resulted in an incentive to over-supply medical services or cause a supplier-induced demand for medical resources.…”
Section: Introductionmentioning
confidence: 99%